The Impediments of Policy Coordination on E-Waste in ASEAN - Ibitz, Armin (Indonesian Journal of International Law, 2012)
ASEAN represents one of the most dynamic economic regions. However, economic progress was accompanied by massive environmental deterioration. Among the many environmental issues in the region, the rapid growth of waste from electronic and electrical equipment (e-waste) has increasingly drawn international attention. While on the one hand ASEAN is a large producer of electrical and electronic equipment, on the other hand the region is heavily affected by the improper dismantling, recycling and disposal of e-waste. ASEAN failed to come up with a common response whereas individual member states pushed ahead with own legislation in an attempt to address the issue. This study sets out to assess the determining factors that disabled ASEAN to agree on a common policy response in the case of e-waste. Based on the assumption that states act according to the expected gains, the study applies a game theoretical approach to analyze the developments. Furthermore, the work seeks to draw conclusions from the case for future environmental policy formation in the region.